2013
DOI: 10.1049/iet-nbt.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanosilica and silicon sources on plant growth promoting rhizobacteria, soil nutrients and maize seed germination

Abstract: The study was aimed at evaluating the effect of nanosilica and different sources of silicon on soil properties, total bacterial population and maize seed germination. Nanosilica was synthesised using rice husk and characterised. Silica powder was amorphous (50 nm) with >99.9% purity. Sodium silicate treated soil inhibited plant growth promoting rhizobacteria in contrast to nanosilica and other bulk sources. Surface property and effect of soil nutrient content of nanosilica treatment were improved. Colony formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 36 publications
7
83
0
5
Order By: Relevance
“…Nanosilica treatment exhibited a better effect than ordinary silica fertilizer application and controls at all observation variables such as plant height, root length, leaf length and root fresh and dry weight of rice plants (Amrullah & Sugianta 2015). Additionally, nanosilica has favorable effects on beneficial bacterial population, nutrient value of soil and seed germination percentage in maize than conventional Si sources (Karunakaran et al 2013). The phytotoxicity of silica nanoparticles was evaluated as a function of concentration (250 and 1000 mg L ¡1 ) toward Arabidopsis thaliana plants.…”
Section: Discussionmentioning
confidence: 99%
“…Nanosilica treatment exhibited a better effect than ordinary silica fertilizer application and controls at all observation variables such as plant height, root length, leaf length and root fresh and dry weight of rice plants (Amrullah & Sugianta 2015). Additionally, nanosilica has favorable effects on beneficial bacterial population, nutrient value of soil and seed germination percentage in maize than conventional Si sources (Karunakaran et al 2013). The phytotoxicity of silica nanoparticles was evaluated as a function of concentration (250 and 1000 mg L ¡1 ) toward Arabidopsis thaliana plants.…”
Section: Discussionmentioning
confidence: 99%
“…MSWC treatments increased soil P content, while it did not show a significant difference between NS treatments with control (p<0.05). Karunakaran et al (2013) reported that the availability of silicon sources (sodium silicate, micron silica, silicic acid, and tetraethyl silicate) might increase available nitrogen, phosphorus, and potassium (NPK) value to some extent, which is not comparable with NS. Thus, the incorporation of NS into soil enhances soil NPK values.…”
Section: Effect Of Mswc and Ns On Ec Ph N K P Om And Cec In Potmentioning
confidence: 98%
“…The reason for the decrease in the pH is probably that hydrated silica is formed through binding the Si-O to water molecules and hence reduces pH. Karunakaran et al (2013) and Iler (1979) found that nanosilica and microsilica shows a slight decrease in pH as they both are slightly soluble in water at ppm range, which is converted to silicon colloids because of hydrogen bonding, making them biologically active molecules. EC was low in MSWC treatments, increased in NS250 treatment it was increased as compared with control and decreased in NS500 treatment.…”
Section: Effect Of Mswc and Ns On Ec Ph N K P Om And Cec In Potmentioning
confidence: 99%
See 2 more Smart Citations